Global Mapping of Strategic Communication Paradigms: A Bibliometric and Thematic Analysis (1970–2025) - Muslem; Masdalifah Sembiring (Fakultas Usluhuddin dan Dakwah UIN Syekh Wasil Kediri, 2026)
This study provides a bibliometric and thematic analysis of global research on strategic communication from 1970 to 2025. Using data from Scopus processed with RStudio (Biblioshiny), 3,953 documents from 976 academic sources were analyzed to identify thematic structures, conceptual evolution, and geographic trends shaping this discipline. The results reveal that strategic communication has evolved from a managerial and public relations perspective into a multidimensional, data- and value-based field that integrates digital technology, ethics, and sustainability. Three dominant clusters were identified: (1) digital communication and public engagement, (2) crisis and risk communication, and (3) sustainability and corporate social responsibility. Thematic evolution reveals a paradigm shift from classical public relations (1970–1990) to integrated marketing communication (2000s) and digital sustainability communication (2010–2025). Research trends highlight an increasing focus on social media, trust, CSR, AI, and sustainability since 2015, marking the emergence of a data-driven, ethical communication paradigm. Geographically, the United States and Western Europe dominate publication output, but growing contributions from Asia—especially China and India—reflect a more diverse, multipolar academic landscape. This study provides theoretical and practical insights for developing globally adaptive and ethically grounded strategic communication frameworks.